Design of Batak Toba Art and Culture Museum Center In The City of Medan By Applying Neovernacular Architecture Themes. - Julius Putra Simbolon; Nelson Siahaan (International Journal of Architecture and Urbanism, 2021)
Medan City is a city that has a variety of cultures and traditions. This diversity can give color to the world of tourism, especially in the city of Medan. One of the customs and cultures in the city of Medan is the Batak Toba, a native of the North Sumatera province. Tourism with high cultural value will make a positive impact on visitors who come to study and recreate in the tourism area, especially this museum. The design involves two different aspects where the design must be able to unite the Vernacular aspects that exist in the existing site as well as the modern touch of Neovernacular Architecture. The diversity of the arts and culture of Batak Toba Culture increasingly supports the achievement of space inside and outside the museum. It attracts visitors to calm the mind, relax, and learn many things about Batak Toba Arts and Culture. The existence of the Batak Toba Arts and Culture Museum is expected to increase the number of local and foreign tourists visiting the area to find out and perverse the Batak Toba culture